Ḍôktara athavā Vaidya yāñcī madata jethẽ miḷanyāsārakhī nasela, tethalyā lok̃āsāṭh̃ī Plegasambandh̃ī thoḍakyānta māhitī - Śirag̃āvakara, Vhī. Je (Śrīrāmatattva Prakāśa, 1905)
Information on home treatment for plague when medical aid is unavailable.